Health of the Food Environment Is Associated With Heart Failure Mortality in the United States. (25th October 2022) - Gondi, Keerthi T.; Larson, John; Sifuentes, Aaron; Alexander, Neil B.; Konerman, Matthew C.; Thomas, Kali S.; Hummel, Scott L.
Abstract : Background: Food environment factors contribute to cardiovascular disease, but their effect on population-level heart failure (HF) mortality is unclear. Methods: We utilized the National Vital Statistics System and USDA Food Environment Atlas to collect HF mortality rates (MR) and 2 county food environment indices: (1) food insecurity percentage (FI%) and (2) food environment index (FEI), a scaled index (0–10, 10 best) incorporating FI% and access to healthy food. We used linear regression to estimate the association between food environment and HF MR Results: Mean county FI% and FEI were 13% and 7.8 in 2956 included counties. Counties with FI% above the national median had significantly higher HF MR (30.7 versus 26.7 per 100 000; P <0.001) compared with FI% below the national median. Counties with HF MR above the national median had higher FI%, lower FEI, lower density of grocery stores, poorer access to stores among older adults, and lower Supplemental Nutrition Assistance Program participation rate ( P <0.001 for all). Lower county FI% (β=−1.3% per 1% decrease) and higher county FEI (β=−3.6% per 1-unit increase in FEI) were significantly associated with lower HF MR after adjustment for county demographic, socioeconomic, and health factors. This association was stronger for HF MR compared with non-HF cardiovascular disease MR and all-cause MR The relationship between food environment and HF MR was stronger in counties with the highest income inequity and poverty rate. Conclusions: Healthier food environment is significantly associated with lower HF mortality at the county level. This reinforces the role of food security on cardiovascular outcomes.